The Role of Inflammasome-Dependent and Inflammasome-Independent NLRP3 in the Kidney - Kim, Yang Gyun (Cells, 2019)
Cytoplasmic nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) forms an inflammasome with apoptosis-associated speck-like protein containing a CARD (ASC) and pro-caspase-1, which is followed by the cleavage of pro-caspase-1 to active caspase-1 and ultimately the activation of IL-1β and IL-18 and induction of pyroptosis in immune cells. NLRP3 activation in kidney diseases aggravates inflammation and subsequent fibrosis, and this effect is abrogated by genetic or pharmacologic deletion of NLRP3. Inflammasome-dependent NLRP3 mediates the progression of kidney diseases by escalating the inflammatory response in immune cells and the cross-talk between immune cells and renal nonimmune cells. However, recent studies have suggested that NLRP3 has several inflammasome-independent functions in the kidney. Inflammasome-independent NLRP3 regulates apoptosis in tubular epithelial cells by interacting with mitochondria and mediating mitochondrial reactive oxygen species production and mitophagy. This review will summarize the mechanisms by which NLRP3 functions in the kidney in both inflammasome-dependent and inflammasome-independent ways and the role of NLRP3 and NLRP3 inhibitors in kidney diseases.